Chapter La ricezione di Dante in Cechia dopo il 1989 - Špička, Jiří (Biblioteca di Studi di Filologia Moderna, 2022)
After 1989, the reception of Dante in the Czech Republic was no longer determined by the ideological control of the regime and became part of an open cultural context, competing with other themes and authors. The milestones of this new era were a new complete translation of the Comedy and the first complete translation of the De vulgari eloquentia, accompanied by other occasional initiatives, the production or translation of texts for the study of Dante and partial translations of Dante's works. The weak point of reception remains the absence of Dante in school curricula.